2014
DOI: 10.1128/jb.01463-13
|View full text |Cite
|
Sign up to set email alerts
|

Influence of O Polysaccharides on Biofilm Development and Outer Membrane Vesicle Biogenesis in Pseudomonas aeruginosa PAO1

Abstract: Pseudomonas aeruginosa is a common opportunistic human pathogen known for its ability to adapt to changes in its environment during the course of infection. These adaptations include changes in the expression of cell surface lipopolysaccharide (LPS), biofilm development, and the production of a protective extracellular exopolysaccharide matrix. Outer membrane vesicles (OMVs) have been identified as an important component of the extracellular matrix of P. aeruginosa biofilms and are thought to contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 58 publications
9
100
1
Order By: Relevance
“…Similarly, while Pseudomonas O-antigen mutants have no effect on the rate of OMV release, they do affect both their contents and size (43). The LPS of V. fischeri cells includes an unusual O antigen that plays a critical role in both flagellar motility and efficient colonization (18), but there is little understanding of this relationship or its relationship to broader changes in either the cell's surface or its OMVs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while Pseudomonas O-antigen mutants have no effect on the rate of OMV release, they do affect both their contents and size (43). The LPS of V. fischeri cells includes an unusual O antigen that plays a critical role in both flagellar motility and efficient colonization (18), but there is little understanding of this relationship or its relationship to broader changes in either the cell's surface or its OMVs.…”
Section: Discussionmentioning
confidence: 99%
“…OMV were isolated mainly following the procedure described previously (30). Briefly, different P. aeruginosa strains were grown in 800 ml TSB (Becton, Dickinson, Mississauga, Ontario, Canada) for 16 h at 37°C in a rotary shaker at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm development was assayed according to previously described methods (30,44). Briefly, each PAO1 migA containing two point mutations, R92Q and V170M; the amino acid sequence is the same as that encoded by PA14 migA This study pHERDrmd pHERD20T vector containing the PA14 rmd gene This study strain was grown in tryptic soy broth (TSB) to an optical density at 600 nm (OD 600 ) of 0.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that alterations of a single band or both bands of the O-antigen of P. aeruginosa PAO1 can give rise to mutants with increased cytotoxicity mediated by the type III secretion system (Augustin et al, 2007). In addition, changes in O-polysaccharide expression in PAO1 affect the size and protein content of outer membrane vesicles, and the formation of a robust biofilm (Murphy et al, 2014).…”
Section: Cross-resistance and Reversibility Of Mutantsmentioning
confidence: 99%